Learners' Perceptions of Generative AI in Chinese Language Learning: A Pilot Study in Irish Higher Education - Wang, Hongfei (My University, 2025)
This pilot study explores the integration of Generative AI, specifically ChatGPT, as a Technology-Enhanced Language Learning (TELL) tool in Chinese as an Additional Language (CAL) education in Irish higher education. The study employs qualitative methods to examine interviews with CAL learners from two consecutive groups of the same master’s programme to assess evolving perceptions, feedback, and engagement with Generative AI. The first group engaged with ChatGPT shortly after its release, demonstrating a mix of curiosity and scepticism regarding its role in CAL language education. In contrast, the second group interacted with the tool in a context of broader acceptance, perceiving it as a standard educational aid and exhibiting increased confidence and reliance on its functionalities. Comparative analysis highlights a growing recognition of Generative AI as a valuable resource, particularly for real-time feedback and language support. However, persistent concerns remain regarding linguistic accuracy and control in Chinese, underscoring the need for further refinement. By adopting a qualitative approach, this study offers insights into the shifting attitudes of CAL learners toward Generative AI, contributing to ongoing discussions on its pedagogical implications. The findings inform future research aimed at enhancing AI-driven language learning tools to optimize educational outcomes while addressing existing limitations. This study thus advances the understanding of Generative AI’s evolving role in facilitating effective Chinese language instruction.
PUBLISHED
Keywords: Chinese; Generative AI; Higher education; Language Technology; Technology-Enhanced Language Learning (TELL); Digital Humanities; Applied Linguistics; Computer Assisted Language Learning (CALL); Education and minority language; LINGUISTICS; Minority language education and maintenance; SECOND LANGUAGE LEARNERS; Second language acquisition; Technology and communication